Socio-economic determinants of obesity of Namibian women in the reproductive age group: A binary logistic regression model (Journal for Studies in Humanities and Social Sciences, 2015)
Obesity leads to reduced lifer expectancy, increased likelihood of a wide range of diseases Obesity also lowers self-esteem and has negative consequences on the cognitive and social development of a person. World-wide, obesity is a leading yet preventable cause of death and its prevalence both in children and adults is increasing day by day. Compared to men, women have a relatively higher burden of disease attributable to overweight and obesity. This paper establishes the socio-economic factors influencing obesity in women in Namibia using logistic regression. The outcome variable was Obesity (1 for Obese, 0 for Not obese). The independent variables included the total number of children ever born to the woman, her place of residence; current age of the woman, her highest level of education, her economic status, contraceptive use, smoking habits, age of the woman at first birth, place of residence, region, and religion. Results indicate that in Namibia, obesity of a woman is associated with the age of the woman, her highest level of education, her economic status, contraceptive use, smoking habits, and the age of the woman at first birth. Policy and intervention programs to reduce obesity should focus on encouraging women to delay onset of child-bearing, to embark on lifelong regular exercise and diet programs. Even though smoking was inversely related to obesity, women should be encouraged to stop smoking because of its other devastating health effects.